A Comprehensive Review of CMOS Analog Circuit Design Techniques for Low-Power VLSI Systems - Heena T Shaikh; Kazi Kutubuddin Sayyad Liyakat (International Journal of VLSI Circuit Design & Technology, 2026)
CMOS analog circuit design plays a significant role in the development of modern low-power Very Large-Scale Integration (VLSI) systems used in wireless communication, biomedical devices, portable electronics, embedded systems, and Internet of Things (IoT) applications. Research on low-power CMOS analogue design methodologies has intensified because to the growing need for high-performance, small, and energy-efficient electronic products. However, reducing power consumption while maintaining signal accuracy, noise performance, stability, bandwidth, and overall circuit reliability remains a major challenge in advanced VLSI systems. A thorough analysis of CMOS analogue circuit design methods for low-power VLSI applications is provided in this review article. The paper discusses fundamental CMOS technologies, analog design methodologies, SPICE modeling, and performance optimization techniques used in modern integrated circuits. Various analog building blocks including operational amplifiers, differential amplifiers, operational transconductance amplifiers (OTA), comparators, voltage references, current sources, and data converters are examined in detail. The study also reviews low-voltage and low-power design approaches, frequency response characteristics, noise reduction methods, and mixed-signal circuit integration techniques. In addition, recent developments in electronic design automation (EDA), RF CMOS circuits, and advanced semiconductor technologies are analyzed. The review concludes that efficient CMOS analog circuit design significantly improves power efficiency, circuit performance, and reliability in next-generation VLSI systems and portable electronic applications.
Keywords: CMOS Analog Circuits; Electronic Design Automation (EDA); Mixed-Signal Integrated Circuits; Operational Transconductance Amplifier (OTA); low-power VLSI